Role of social and behavioral factors in prevention of hypertension in Godawari municipality of Lalitpur district. - Maharjan,Sophiya (2019)
ABSTRACT: Background: Hypertension is defined by systolic blood pressure (SBP) ≥140 mmHg and/or diastolic blood pressure (DBP) ≥90 mmHg. Hypertension is one of the major cardiovascular problems in middle and low income countries leading to kidney failure, blindness, rupture of blood vessels and cognitive impairment. The risk factors of hypertension can be age, sex, literacy, dietary habits, smoking tobacco, alcoholism etc. also determined by many social, economic and environmental aspects. Methodology: The study was carried out with the objective to study the association between socio-demographic and behavioral factors associated with hypertension in Godawari Municipality of Lalitpur district. A cross sectional study design was used to conduct the study. It was conducted in Godawari Municipality of Lalitpur district from Ashar 2075 to Baisakh 2076. Multistage sampling technique was used for the selection of sample. The sample size of the study was 227 subjects of age group 15 to 69 years. Findings: Data collection was done by the preparation of structured questionnaires and the analysis was done by the use of SPSS 20, and Ms Office. According to the study there were (52.4%) female and (47.6%) male respondents, with 57.7% of age group 45-69 years, followed by 25.6% of age 30 to 44 years. Among the subjects 42.8% reported of recommended for high blood pressure. Socio-demographic factors, age factor with p value (0.001), and occupation of respondents with p value (0.038) were found highly associated with hypertension. Behavioral factors like drinking alcohol with p value .015, vigorous and moderate workplace activities with p value 0.010 and 0.035 respectively were found highly associated with hypertension. Conclusion: The prevalence of both hypertension is (42.8%) high in Godawari Municipality of Lalitpur district. This makes the people of this area vulnerable to several chronic diseases and other unbearable health consequences. Both men and women are at risk of being hypertensive. Identification of these risk factors at an early stage of life is an important opportunity for primary prevention of hypertension. Strengthening health education programs promoting hypertension awareness, and emphasizing preventive measures needs to be highly focused. Keywords: Hypertension, Risk factors, Social and behavioral factors.